INCREASING SOME FLAVONOIDS COMPOUNDS FOR ECHINACEA PURPUREA L. USING COPPER OXIDE NANOPARTICLES IN VITRO. - M. H. Ahmed,; Z. S. Omran,; A. G. Oraibi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to increase some flavonoids active compounds production in Echinacea purpurea seedlings through plant seeds treatment with different concentrations of copper oxide nanoparticles that daignosed and characterized using AFM technique. This research was implemented at plant tissue culture labrotary  of College of biotechnology - Al Nahrain University, during the period of 2021 and 2023. The experiment designed factorial within CRD using three factors and ten replicates (3X3). Sodium hypochlorite concentration (S1, S2, S3, S4) (0.0, 1, 2, 3%) represented the first factor, treatment duartion time (T1, T2, T3) (5, 10, 15min) represented the  second factor and copper oxide nanoparticles concentrations (C1, C2, C3, C4) (0.0, 25, 50, 75mg/ml) represented the  third factor. Results showed that the full reduction in the contamination rate of the selected E. purpurea explant recorded in 3% sodium hypochlorite at 10 and 15min. The results also showed that there were a significant increase in the shoots numbers in 50mg/ml CuNPs that recording the highest shoots numbers, the shoot length increased significantly within the 25mg/ml recording 13.5cm then decreased in 50 and 75 mg/ml and the seedlings dry weight increased significantly up to 50mg/ml CuNPs that recording the highest seddlings dry weight, then the seedlings dry weight also decreased significantly in 75mg/ml  CuNPs. Also, all the analyzed flavonoids compounds using HPLC device as Echinolone,  Humulene, Coumarin, Myricetin, Heperidin and Naringin concentrations were significantly increased in 50 and 75 mg/L-1 Cu ONPs, except the  Humulene and Coumarin compound that significantly decreased in 75 mg/L-1 Cu ONPs in comparsion to the control.